2020
DOI: 10.1161/jaha.119.014398
|View full text |Cite
|
Sign up to set email alerts
|

Walking Route–Based Calculation is Recommended for Optimizing Deployment of Publicly Accessible Defibrillators in Urban Cities

Abstract: Background A straight line–based model is often used to calculate the distance between an out‐of‐hospital cardiac arrest ( OHCA ) and the location of an automated external defibrillator ( AED ). This model may be inaccurate as it overlooks any obstacles between the OHCA and AED . This study aimed to elucidate the effect of the straight line–based and walking route–based cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“… 6 Researchers in Hong Kong demonstrated substantially increased travel distances between 5119 historical OHCAs and 1637 public-access AEDs using real-world estimates rather than straight-line estimates. The average increased from 231 m to 543 m. 7 …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“… 6 Researchers in Hong Kong demonstrated substantially increased travel distances between 5119 historical OHCAs and 1637 public-access AEDs using real-world estimates rather than straight-line estimates. The average increased from 231 m to 543 m. 7 …”
Section: Discussionmentioning
confidence: 96%
“… 6 In Hong Kong, calculating actual walking distance increased the average distance from an OHCA to the nearest AED from 231 m to 545 m, and reduced the proportion of AEDs within 100 m from 30% to 11%. 7 In Italy, the geographical area that an AED covered was similar comparing a 200 m walking distance with a 100 m radius. 8 Travel modality and speed will also affect an AED’s effective coverage area.…”
Section: Introductionmentioning
confidence: 99%
“…However, we calculated distances as straight line, which most likely have underestimated the distances compared with real‐world route distances. Previous studies have shown that route distances are ≈1.3 to 2.4 times longer than straight‐line distances, 13 , 14 and routes for citizen responders might be unwalkable because of water or terrain. 15 Traveling a longer distance could increase the risk of getting injured.…”
Section: Discussionmentioning
confidence: 96%
“…For simplicity, we modelled circular coverage areas around AEDs, whereas it is possible to model more realistic walking-routes based on road/path networks. 39 We did not distinguish cardiac arrests based on demographic and arrest characteristics, other than stratifying by arrests in public locations versus private residences. We treated proximity as a binary variable – whereby an OHCA case was considered to have AED coverage if one or more AEDs were within a threshold distance of the arrest, regardless of the distance within or beyond that threshold.…”
Section: Discussionmentioning
confidence: 99%